Improving Productivity of Pulses in Rice Fallows - Ali, Masood (Indian Farming, 2015)
Malnutrition prevalent in India is due to a number of factors, lack of protein in the diet being one of them. In many Indian states lowland kharif sown rice areas remain uncropped during rabi season, due to various reasons. Crop productivity in rice fallows is generally poor due to vaious biophysical, biotic and abiotic stresses, poor crop management practices and socio-economic reasons. In these rice fallows, it has been found that pulses are ideal to be grown and can be introduced on account of low input requirements, short duration and ability to establish with surface broadcast in standing rice fields. If pulses are cultivated in rice fallows, their additional output/ production will cut foreign exchange incurred on the import and provide nutritional security to the large section of poor people in the society.